Understanding the biochemical characteristics of struvite bio-mineralising microorganisms and their future in nutrient recovery. (May 2020) - Leng, Yirong; Colston, Robert; Soares, Ana
Abstract: The biochemical properties of selected microorganisms ( Bacillus pumilus, Brevibacterium antiquum, Myxococcus xanthus, Halobacterium salinarum and Idiomarina loihiensis ), known for their ability to produce struvite through biomineralisation, were investigated. All five microorganisms grew at mesophilic temperature ranges (22–34 °C), produced urease (except I. loihiensis ) and used bovine serum albumin as a carbon source. I. loihiensis was characterised as a facultative anaerobe able to use O2 and NO3 as an electron acceptor. A growth rate of 0.15 1/h was estimated for I. loihiensis at pH 8.0 and NaCl 3.5% w/v. The growth rates for the other microorganisms tested were 0.14–0.43 1/h at pH 7–7.3 and NaCl ≤1% w/v. All the microorganisms produced struvite, as identified by morphological and X-ray Powder Diffraction (XRD) analysis, under aerobic conditions. The biological struvite yield was between 1.5 and 1.7 g/L of media, the ortho-phosphate removal and recovery were 55–76% and 46–54%, respectively, the Mg 2+ removal and recovery was 92–98% and 83–95%, respectively. Large crystals (>300 μm) were observed, with coffin-lid and long-bar shapes being the dominant morphology of biological struvite crystals. The characterisation of the biochemical properties of the studied microorganisms is critical for reactor and process design, as well as operational conditions, to promote phosphorus recovery from waste streams. Highlights: The five microorganisms tested grew at mesophilic temperatures and pH 7-8. Four of the five microorganisms produced urease and preferred protein as a carbon source. Biological struvite production was linked with microbial growth. Biological struvite crystals were dominantly of coffin-lid and long-bar morphology. Phosphorus and magnesium were removed from the media and recovered as struvite.